Forecasting currency risk in an enterprise using the Monte Carlo simulation - Kaczmarzyk, Jan (Prognozowanie ryzyka walutowego w przedsiębiorstwie z wykorzystaniem symulacji Monte Carlo, 2018)
A non-financial enterprise with receivables or liabilities denominated in a foreign currency is exposed to currency risk. Wanting to calculate a financial reserve in order to secure its receivables or liabilities, an enterprise can introduce the concept of the value at risk. To determine value at risk, an enterprise has to know the probability distribution of the future value of the receivable or the liability for a specific moment in future. Using a geometric Brownian motion to reflect exchange rate changes is among the possible solutions. The aim of the paper is to indicate that using the Monte Carlo simulation for forecasting the currency risk of an enterprise is a clear, easy-to-implement and flexible in terms of the assumptions approach. The flexibility of the Monte Carlo approach relies on the possibility to take up the assumption that the currency position changes caused by currency fluctuations have an other than normal probability distribution
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 4, s. 50-63
Keywords: corporate finance; financial risk; risk analysis; Monte Carlo